Development of cadmium sulfide quantum dots-polyamidoamine dendrimer thin films for detection of dengue virus E-protein antigens - Sheh Omar, Nur Alia; Yap, Wing Fen; Abdullah, Jaafar; Mustapha Kamil, Yasmin; Saleviter, Silvan; Mahdi, Mohd Adzir (2018)
In this work, cadmium sulfide quantum dots composited with polyamidoamine (PAMAM) dendrimer (CdSQDs-PAMAM) thin film had been successfully developed for use in the detection of DENV E-proteins. The SPR results suggested that DENV E-protein can be detected in the range 0.0001 to 10 nM. The successful binding between antibodies and antigens in an immunoassay sensor was further confirmed using UV-Vis spectroscopy, by observing the red shift of absorption edge.